Ventilation influence in occupational exposure to fungi and volatile organic compounds: poultry case - Viegas, Carla (2012)
Introduction - In poultry houses, large-scale production has led to increased bird densities within buildings. Such high densities of animals kept within confined spaces are a source of human health problems related to occupational organic dust exposure. This organic dust is composed of both non-viable particles and viable particulate matter (also called bioaerosols). Bioaerosols are comprised by airborne bacteria, fungi, viruses and their by-products, endotoxins and mycotoxins. Exposure to fungi in broiler houses may vary depending upon the applied ventilation system. Ventilation can be an important resource in order to reduce air contamination in these type of settings. Nevertheless, some concerns regarding costs, sensitivity of the animal species to temperature differences, and also the type of building used define which type of ventilation is used. Aim of the study - A descriptive study was developed in one poultry unit aiming to assess occupational fungal and volatile organic compounds (VOCs) exposure.